A time-space decomposition method for fast calculations of transient pressure fields generated by ultrasound phased arrays - Kelly, James F.; McGough, Robert J. (Canadian Acoustics, 2005)
A rapid single integral approach has been developed for computing the time domain pressure generated by a baffled circular piston. A time domain solution to the lossless wave equation can be derived subject to an input pulse, which models the uniform normal velocity of the piston. A linear array of 129 circular elements is simulated with pistons of radius (0.30mm) and interelement spacing (0.90mm). It is concluded that an exact time-domain solution forms the basis for array simulations, which is accelerated by decomposing the spatial dependence of the integrand.